Photodynamic Therapy Effects with Curcuma longa L. Active Ingredients in Gel and Blue LED on Acne: A Randomized, Controlled, and Double-Blind Clinical Study - Jaqueline de Souza Crusca; Luis Henrique Oliveira de Moraes; Thiago Gomes Figueira; Nivaldo Antonio Parizotto; Gerson Jhonatan Rodrigues (Photonics)
Photodynamic therapy (PDT) using the photosensitizer curcumin and blue light has a relevant effect on bacteriological decontamination caused by C. acne. The aim is to verify PDT’s effectiveness with curcumin in individuals diagnosed with moderate to severe acne. This study was carried out on a total of 35 volunteers of both genders (12–32 years old), with moderate to severe acne vulgaris. The volunteers were randomized into five groups: L (LED), V (Vehicle), C (Curcumin), L + V (LED + Vehicle), and L + C (LED + Curcumin). The curcumin gel and LED with blue wavelength (450 nm ± 10 nm) were used. Qualitative and quantitative evaluations were used to verify the efficacy of the treatment by counting inflamed and non-inflamed lesions. The L + C group until day 30 showed a lower percentage of inflammatory lesions than the Vehicle group for the same period. On day 60, the L + C group showed lower inflammatory lesion values compared to the other groups. Intragroup analysis of hydration in the Vehicle group (V) showed a difference on days 30 and 60 compared to day zero. In an intragroup analysis, the L + C group showed a decrease in the mean scores on day 30, and day 60 compared to day zero, showing an improvement in the psychosocial status of these volunteers. Taken together, our results showed that the combination of blue LED therapy and curcumin proved to be an effective and safe treatment for reducing inflamed acne lesions in individuals with moderate to severe acne, while also enhancing their quality of life from a psychosocial perspective.